1994
DOI: 10.1530/jrf.0.1000291
|View full text |Cite
|
Sign up to set email alerts
|

A description of the basic system of components in pregnant mice sera responsible for 'early pregnancy factor' activity

Abstract: The supernatant and pellet retentate fractions obtained from sera from pregnant mice by ammonium sulfate fractionation and extensive dialysis cannot alone induce increased rosette inhibition titres in the rosette inhibition assay. In combination, however, the mixtures can induce increased rosette inhibition titres mimicking the activity of pregnancy sera previously ascribed to the early pregnancy factor. The studies described herein demonstrated that the supernatant retentate fractions derived from sera of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The possible involvement of this powerful redox control system in reproductive processes is of particular interest since the discovery of its role in the``early pregnancy factor'' system (Clarke et al, 1991;Tonissen et al, 1993;Orozco et al, 1994). More recently using immunocytochemical techniques to localise thioredoxin in the early human placenta, we (Perkins et al, 1995) and others (Kobayashi et al, 1995) found very high and speci®c expression of thioredoxin by the cytotrophoblast cells.…”
Section: Introductionmentioning
confidence: 81%
“…The possible involvement of this powerful redox control system in reproductive processes is of particular interest since the discovery of its role in the``early pregnancy factor'' system (Clarke et al, 1991;Tonissen et al, 1993;Orozco et al, 1994). More recently using immunocytochemical techniques to localise thioredoxin in the early human placenta, we (Perkins et al, 1995) and others (Kobayashi et al, 1995) found very high and speci®c expression of thioredoxin by the cytotrophoblast cells.…”
Section: Introductionmentioning
confidence: 81%
“…Among the number of possible embryo-derived signals known to regulate the endometrial response to the pre-implanting embryo (PIF, EPF, EGF, interleukins, hCG) [11,12], we will recapitulate here some of the recent insights about hCG and signal transduction systems of uterine receptivity. A possible interfering action on this signal transduction is played by gonadotropins used for controlled ovarian hyper-stimulation (COH).…”
Section: Introductionmentioning
confidence: 99%
“…This multifactorial model of the capacity of pregnancy serum to express activity in the bioassay,' rather than needing to "be reinterpreted" (10), has now been substantiated by recent studies (6,11) which defined in principle the basic set of components required, and which explained many of the previously enigmatic characteristics of "EPF" as simply properties of the system of components responsible for activity expression.…”
mentioning
confidence: 99%
“…No; it has never been suggested so. Rather, thioredoxin has been shown to be a permissive factor in the system of components that ensures activity expression (11). Chaperonin 10 may be another of the required components.…”
mentioning
confidence: 99%